A study of grass silage preservation with particular reference to the use of sodium metabisulphite as an additive : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the University of New Zealand - Smith, William Campbell (Massey University, 1957)
The problems of preserving roughages for the feeding of livestock using unfavourable periods of pasture growth are perennial. The preservation of legumes and grasses as hay of high quality is governed mainly by two factors: ideal curing weather and stage of maturity of the crops. The inability of the farmer to control these factors results in heavy nutrient losses in the days during the curing process. The development of an alternate process of preservation has been the objective of investigators for many years. Artificial drying of protein rich herbage results in the best preservation with least storage loss but, as yet, the process involves a large capital outlay and high operating costs. This at present eliminates it from consideration by the average farmer. The preservation of early harvested material as silage seems to be the most logical approach to the solution of the problem because of the high efficiency of the process for timely handling.
Keywords: Silage